Physical fitness and anthropometric profiles of the Turkish special athletes national swimming team - Ince, G.; Turkeri, C. (Sport Science - International Scientific Journal of Kinesiology, 2016)
This study examines physical fitness and anthropometric profiles of the Turkish Special Athletes National Swimming Team. A total of twenty-two swimmers, (7 female and 15 male), (9 with mild mental retardation, 8 with down syndrome, and 5 with mild autism) in the Turkish Special Athletes National Swimming Team has participated in this study. The mean ages of the participants were 18.14±4.04 years. The mean body weights were 60.58±14.85 kg, the mean heights were 160,14±12,56 cm. The means of the number of years in sport were 4.73±3.54 years. The means of the number of years in the branch were 3.91±3.21years. In this study, physical fitness measurements (spine flexibility, balance, vertical jumping, standing long jump, right-left hand reactions), anthropometric measurements: upper extremity measurements, lower extremity measurements, width measurements, and circumference measurements were performed. Flexibility of the spine was measured by inclinometer device, hand reaction was found by nelson hand reaction test, balance, bass stick to the measurement of balance (lengthwise) test, the measurement of the length and depth of the chest, sliding caliper, environmental measurements, measuring tape, sitting height measuring board were used to sitting height. Statistical analysis, SPSS 11.5 package program was performed. Statistical results of the measurements, mean, standard deviation, and frequency distributions were determined. Disability status and the relationship between physical fitness and anthropometric measurements were determined by one way Anova and kruskal wallis test. The result of the statistical measurements indicates differences concerning participants` average dip widths, upper arm, forearm, hand length, upper leg and the leg length, foot length, shoulder and chest widths (p <0.01). Consequently, this study`s results can help swimming coaches to evaluate physical fitness and anthropometric measurements of their athlete swimmers with intellectual disabilities.